DESAIN PENELITIAN DALAM PERSPEKTIF PENDIDIKAN - Tresna, Popy Wulandari; Hayadi, Bambang Herawan; saputra, Dicky wahyu; Fitriani, Pina; Samsuri, Samsuri; Salbiah, Siti (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
This study conceptually examines research design from the perspectives of education and learning, as well as the functional relationship between them. The method employed is library research with a descriptive qualitative approach, through literature review from various credible academic sources published between 2021 and 2025. The findings indicate that research design in education serves as an epistemological foundation that systematically directs the scientific process, encompassing approaches such as action research, research and development, and both qualitative and quantitative methods. Meanwhile, research design in learning is more applicative in nature, focusing on designing and testing the effectiveness of teaching and learning processes contextually and measurably. The relationship between the two is reciprocal and mutually reinforcing, where findings from educational research directly inform improvements in instructional design in the field. The integration of technology, such as artificial intelligence and virtual reality, has also broadened the horizon of research design toward a more adaptive and multidisciplinary direction. This study affirms the importance of a holistic understanding of research design as a strategic instrument in continuously improving the quality of education